Análise térmica de insertos revestidos e não revestidos no torneamento a seco para diferentes velocidades de avanço - Vieira, Gustavo Cassiano (Universidade Federal de São Carlos, 2025)
Turning is used in the production of parts with rotational geometry, providing dimensions, tolerances and surface finishes suitable for their applications. One of the main factors that guarantee the final quality of the turned product is the cutting tool. During material removal the tooling is subjected to high temperatures, which accelerates its wear compromising the properties of the workpiece produced. In order to slow down the deterioration of the insert, thin layers of coating are applied to its surfaces to reduce the thermal gradients inside it and extend its service life. Predicting the thermal field during the cutting process is essential for estimating the ideal time for tool replacement. In this context, the present study aimed to analyse the temperature field behaviour of a carbide insert (WC-Co) with and without coating (AlTiN) for different feed rates. The study used the finite element method to perform thermal simulations based on simplifying assumptions. The entire thermal modelling process was carried out, from determining the cutting force and cutting power to the thermal properties of the materials and contact resistance. The main results analysed were the temperature fields obtained through numerical simulation, as well as the heating curves and temperature profile along the cutting edge.
Thermal analysis of coated and uncoated inserts in dry turning for different feed rates
Keywords: Análise térmica; Torneamento; Ferramenta de corte; Thermal analysis; Turning; Cutting tool; ENGENHARIAS::ENGENHARIA MECANICA; 9. Indústria, Inovação e Infraestrutura